2013
DOI: 10.3402/qhw.v8i0.20194
|View full text |Cite
|
Sign up to set email alerts
|

Self-respect through ability to keep fear of frailty at a distance: Successful ageing from the perspective of community-dwelling older people

Abstract: With population ageing, there is an increased interest in how to promote a good old age. A predominant concept in these discussions is successful ageing, which is mainly based on researchers’ definitions. This article aims to explore successful ageing from the perspective of community-dwelling older people (24 persons aged 77–90 years). Individual open interviews were conducted and analysed according to qualitative content analysis. An overarching theme was formulated as “self-respect through ability to keep f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 46 publications
6
84
0
1
Order By: Relevance
“…In terms of use of care this could include referral to services, with an emphasis on preference for services that would enable them to maintain their independence and ‘keep frailty at a distance’ [51]. …”
Section: Resultsmentioning
confidence: 99%
“…In terms of use of care this could include referral to services, with an emphasis on preference for services that would enable them to maintain their independence and ‘keep frailty at a distance’ [51]. …”
Section: Resultsmentioning
confidence: 99%
“…Ramirez et al (2014) found reductions in anxiety and depression after elderly participants wrote letters expressing their gratitude to other. Hörder et al (2013) Perceived stress scores significantly reduced over the course of the intervention but this reduction was not maintained at follow up with scores returning close to those at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report that the association of a gratitude intervention with reductions in depression supports the finding of Seligman, Steen, Park and Peterson (2005) and Gander, Proyer, Ruch, and Wyss (2012), although the participants were younger in these studies. A qualitative interview study exploring successful ageing with 24 community-dwelling older people aged between 77 and 90 years, reported that the strategy of choosing to feel gratitude for what was positive in their lives rather than worrying about what they cannot change was associated with increased feelings of well-being (Hörder, Frändin, & Larsson, 2013).…”
Section: Gratitude and The Elderlymentioning
confidence: 99%
“…There is evidence showing empirically that this relationship between feeling gratitude and well-being is causal (Emmons and Shelton 2002;Horder et al 2013;Ramirez et al 2014). For instance, Rash et al (2011) found that gratitude interventions contributed most to all the aspects of well-being of an individual.…”
Section: Discussionmentioning
confidence: 87%